Hubungan Tingkat Pengetahuan Tentang Pola Makan Terhadap Sikap Pencegahan Kekambuhan Artritis Gout Di Posyandu Lansia Bagas Waras Kartasura - Ramadoan, Febrian Andani; , Arina Maliya S.Kep., Ns.,.M.Si.Med (2016)
Gouty arthritis is the end product of purine metabolism. Uric acid circulating in the human body to be manufactured by the body. Gout patient attitude factor in maintaining the levels of uric acid in her dealing with the prevention of recurrence of gout. Knowledge of gout patients on proper diet is one of the factors that shape attitudes towards patients with gout diet gout patients. This study aims to determine the relationship of the level of knowledge about the diet of the attitude of gouty arthritis in the prevention of recurrence in IHC Bagas Sane Kartosuro. This research is an analytic observational with cross sectional approach. Collecting data using questionnaires, while data analysis using Chi Square test. Conclusion of the study shawed the knowledge about diet was less, the attitude of gouty arthritis was negative, and the there was correlation level of knowledge about the diet of the attitude of arthritis gout recurrence prevention in elderly Posyandu Elderly Bagas Sane Kartasura, where the better knowledge of the elderly, the attitude is getting better (2obs= 10.099; p-value = 0.001).